2016
DOI: 10.1007/s41024-016-0006-5
|View full text |Cite
|
Sign up to set email alerts
|

Wind-driven rain incidence parameters obtained by hygrothermal simulation

Abstract: The association of rain and wind composes wind-driven rain (WDR), and its incidence may be crucial to the emergence of anomalies on the facades of buildings. Moisture from the WDR can influence the humidification and drying process, therefore the durability and hygrothermal performance are conditioned by the amount of incident water. The quantification of WDR can be an indispensable tool for understanding its related phenomena and the service life of buildings. The most widely used methods of quantification ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 14 publications
2
12
0
3
Order By: Relevance
“…is the coefficient dependent on the vertical distance of the component from the ground (R2 = 0.07 up to 10 m of height [66]), V [m/s] is the average hourly wind speed at 10 m height, and ψ [ • ] is the angle between the wind direction and the normal to the façade. The WDR data are displayed in Fig.…”
Section: Wind-driven Rainmentioning
confidence: 99%
“…is the coefficient dependent on the vertical distance of the component from the ground (R2 = 0.07 up to 10 m of height [66]), V [m/s] is the average hourly wind speed at 10 m height, and ψ [ • ] is the angle between the wind direction and the normal to the façade. The WDR data are displayed in Fig.…”
Section: Wind-driven Rainmentioning
confidence: 99%
“…The literature review on the degradation of building façades reveals that moisture is one of the main factors for materials' deterioration [51]. Wind and solar radiation are responsible factors for moisture settling on the façade and are variable in accordance with the geographical orientation [52]; hence, an analysis of the degradation curves according to the claddings' orientation seems relevant for the analysis of the degradation over time of stone claddings, and they are illustrated in Figure 14. According to Gaspar and de Brito [14], regarding the rate of the erosion process according to the façades' orientation, the authors concluded that north and west are the most critical orientations in Portugal.…”
Section: Analysis Of the Degradation Evolution According To Claddings' Characteristicsmentioning
confidence: 99%
“…External renders are critical in the construction as they are the first barrier to degradation agents and play an important role in water-tightness, thermal insulation, masonry, and structure protection by exerting a decisive influence on their durability [1,2]. However, over time, renders suffer a gradual reduction in their performance in terms of their protective characteristics due to climate agents of degradation [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%